Effects of microclimate on bolete species richness and biomass in a Northern Benin woodland. (27th December 2021) - Badou, Sylvestre A.; Houdanon, Roel D.; Tchan, Kassim I.; Olou, Boris A.; Yorou, Nourou S.
Abstract: Studies examining the role of abiotic variables on fructification sequences of ectomycorrhizal symbionts (boletes), the extent and direction of these effects are quite rare in Africa. In the current study, we assessed the effects of microclimate on the distribution and productivity of boletes in Benin. Nine permanent plots of 2500 m 2 each split into 25 subplots of 100 m 2 were installed in three different vegetation types. The first vegetation type is dominated by Isoberlinia doka, the second by Isoberlinia tomentosa and the third by Uapaca togoensis . Abiotic variables, including soil temperature, air temperature, air relative humidity and soil moisture, were recorded every 30 min from June to October. Each plot was surveyed twice a week during the mushroom season over 3 years (2015, 2016 and 2017) to record the abundance and the fresh biomass. The effects of microclimate on boletes productivity were evaluated using generalised linear mixed models in R. Boletes give the largest natural production in July and the lowest in October. Only soil moisture has a significant negative influence on the abundance ( p  > 0.05). The fruiting periods of boletes are known according to the variability of the microclimatic parameters and the vegetation. Résumé: Les études examinant le rôle des variables abiotiques sur les séquences de fructification des symbiotes ectomycorhiziens (bolets), l'étendue et la direction de ces effets sont assez rares en Afrique. Dans la présente étude, nous avons évalué les effets du microclimat sur la distribution et la productivité des bolets au Bénin. Neuf placeaux permanents de 2 500 m 2 chacune divisées en 25 placettes de 100 m 2 ont été installées dans trois types de groupéments végétaux différents. Le premier type de végétation était dominer par Isoberlinia doka, le second par Isoberlinia tomentosa et le troisième par Uapaca togoensis . Les variables abiotiques, notamment la température du sol et la température de l'air, l'humidité relative de l'air et la teneur en eau du sol, ont été enregistrées toutes les 30 minutes de Juin à Octobre. Chaque placeau a été prospecté deux fois par semaine pendant la saison des champignons sur trois ans (2015, 2016 et 2017) pour enregistrer la présence/absence et la biomasse fraîche des bolets. Les effets du microclimat sur la productivité des bolets ont été évalués à l'aide des modèles mixtes linéaires généralisés dans R. Les bolets donnent la plus grande production naturelle en juillet et la plus faible en octobre. Seule l'humidité du sol a une influence négative significative sur l'abondance des bolets ( p > 0, 05). Les périodes de fructification des bolets sont connues en fonction de la variabilité des paramètres microclimatiques et de la végétation.